International border restrictions and rules toward the illicit trafficking of cultural heritage in the tourism context: A multi-methods approach - Al-Ansi, A.; Han, H.; Loureiro, S. M. C. (Journal of Travel and Tourism Marketing, 2021)
The flourished art market has promoted the process of illicit trafficking of cultural heritage treasures across the world. Our research attempted to evaluate the ambiguity behind this active illegal market. It investigates the performance and restrictions imposed by authorities on their borders to combat the smuggled cultural artefacts and heritage antiques through assessing the local residents’ perceptions and their sustainable responses. The findings reveal the homogeneity between local residents’ sustainable behaviour and their views toward fighting this critical global phenomenon. Additionally, the metric invariance assessment demonstrates the vitality of community participation as an active force in combating illegal activities.